Answer:
[tex](x+1)^2+(y+4)^2=(6\sqrt{2})^2[/tex]
Step-by-step explanation:
The length of the diameter[tex](d)[/tex] will be the distance between [tex](5,-10)\ and\ (-7,2).[/tex]
[tex]d=\sqrt{(2-(-10))^2+(-7-5)^2}=\sqrt{(12)^2+(-12)^2}=\sqrt{144+144}=\sqrt{288}\\\\d=12\sqrt{2}[/tex]
Radius:
[tex]radius(r)=\frac{diameter}{2}=\frac{12\sqrt{2}}{2}=6\sqrt{2}[/tex]
Centre:
Let [tex](a,b)[/tex] be centre of the circle.
Centre will be the mid point of end points of diameter.
[tex]a=\frac{5-7}{2}=\frac{-2}{2}=-1\\\\b=\frac{-10+2}{2}=\frac{-8}{2}=-4\\\\Centre=(-1,-4)[/tex]
Equation of circle:
If [tex](a,b)[/tex] be centre and [tex]r[/tex] be the radius.
Equation of circle: [tex](x-a)^2+(y-b)^2=r^2[/tex]
Here [tex](a,b)=(-1,-4)\ and\ r=6\sqrt{2}[/tex]
[tex](x-(-1))^2+(y-(4))^2=(6\sqrt{2})^2\\(x+1)^2+(y+4)^2=(6\sqrt{2})^2[/tex]